2009
DOI: 10.1166/jnn.2009.m71
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch Synthesis with Fe/Cu/La/SiO<SUB>2</SUB> Nano-Structured Catalyst

Abstract: Nano-structure Fe2O3, CuO and La2O3 components were prepared by micro-emulsion method and then Fe/Cu/La/SiO2 nano-structure catalyst was prepared by mixing and re-slurring the mixture by tetraethylorthosilicate (TEOS). The catalyst composition was designated in term of the atomic ration as: 100Fe/5.64Cu/0.1La/19Si. Structural characterization of nano-structured Fe2O3, CuO and La2O3 components was performed by Transmission Electron Microscopy (TEM), powder X-ray diffraction, Temperature Programmed Reduction (TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The study of Iron oxides nanoparticles has attracted intensive attention over the past decades due to the potential applications in catalysis [18,19]. Recent studies showed nanosized iron particles are widely appearing to be economically feasible on an industrial scale for Fischer-Tropsch process [20][21][22]. In other report immobilized Iron (III)-substituted polyoxotungstates is found effective catalysts for solvent-free aerobic oxidation of n-hexadecane [23].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Iron oxides nanoparticles has attracted intensive attention over the past decades due to the potential applications in catalysis [18,19]. Recent studies showed nanosized iron particles are widely appearing to be economically feasible on an industrial scale for Fischer-Tropsch process [20][21][22]. In other report immobilized Iron (III)-substituted polyoxotungstates is found effective catalysts for solvent-free aerobic oxidation of n-hexadecane [23].…”
Section: Introductionmentioning
confidence: 99%
“…The precursors of the nano structure catalysts were prepared by coprecipitation in a water-in-oil microemulsion as described previously [11][12][13][14][15][16][17]. Similarly Fe/Cu/La catalyst precursors in microemulsion system were precipitated in the same semi-batch reactor.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Since the catalytic properties of the nanoparticles depend on the size, nanoparticles with different sizes are expected to have different catalytic activity and selectivity. The dynamic surface of nanoparticles also depends on the size: smaller nanoparticles have higher surface energy and thus more prone to surface reconstruction, which can lead to different catalytic dynamics for nanoparticles with different sizes [11][12][13][14][15][16][17][29][30][31][32].…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%
See 2 more Smart Citations